Understanding determinants of farmers’ investments in sustainable land management practices in Ethiopia: review and synthesis - Adimassu, Zenebe; Langan, Simon J.; Johnston, Robyn M. (Springer, 2016)
Although there has been several efforts made to reduce land degradation and improve land productivity in Ethiopia, farmers’ investments in sustainable land management (SLM) remain limited. Nevertheless, the results regarding determinants of farmers’ investments in SLM have been inconsistent and scattered. Moreover, these factors have not been reviewed and synthesized. Hence this paper reviews and synthesizes past research in order to identify determinants that affect farmers’ investments in SLM practices and thereby facilitate policy prescriptions to enhance adoption in Ethiopia, East Africa and potentially wider afield. The review identifies several determinants that affect farmers’ investments in SLM practices. These determinants are generally categorized into three groups. The first group is those factors that are related to farmers’ capacity to invest in SLM practices. The results show that farmers’ investments in SLM practices are limited by their limited capacity to invest in SLM. The second groups of factors are related to farmers’ incentives for investments in SLM practices. Farmers’ investments in SLM are limited due to restricted incentives from their investments related to land improvement. The third groups of factors are external factors beyond the control of farmers. The review also shows that farmers’ capacities to invest in SLM and their incentives from investments have been influenced by external factors such as institutional support and policies. This suggests that creating enabling conditions for enhancing farmers’ investment capacities in SLM and increasing the range of incentives from their investment is crucial to encourage wide-scale adoption of SLM practices.